Hydrochemical and stable isotopes (δ2H and δ18O) changes of groundwater from a spring induced by local earthquakes, Northwest China - Xiang, Yang; Peng, Suping (Frontiers in Earth Science, 2023)
It has been well reported that earthquakes can cause changes in groundwater chemistry and isotopes, and much of those changes were occurred in wells or hot springs; however, changes in cold spring caused by local small earthquakes have received less attention. Here, we collected continuous monitoring of the X10 spring (September 2018 to December 2019), investigated the hydrogeochemical characteristics of the spring by using water chemistry analysis and isotope methods. We compared the changes in water chemical ion concentrations and hydrogen-oxygen isotope ratios with the surrounding seismic activity, and the results show that 1) major chemical ion concentrations in X10 springs have an annual dynamic pattern of being high in winter and low in summer, and this change may be related to the seasonal effect of snowmelt; 2) the spring water originates from long-distant meteoric water, snowmelt, and bedrock fissure water and is affected by rock weathering and evaporation; 3) the hydrogen and oxygen stable isotope ratios and HCO3− concentration in groundwater are sensitive to local small seismic activity. We considered that small earthquakes can change the permeability in fault zones or aquifers, leading to mixing of groundwater with different chemical composition and isotopes. Our study demonstrates that the hydrogen and oxygen stable isotopes are more sensitive to seismic activity than the commonly used chemical constitutents, and that the sensitive constitutents vary in different observation wells or springs; therefore, combined monitoring of isotopes and water chemistry should be considered in the future to capture hydrogeochemical precursor signals caused by earthquakes.